Komparasi Teknik Effleurage Massage terhadap Penurunan Skala Nyeri pada Ibu Post Partum - Sitinjak, Netty Fransiska; Supriadi, Supriadi; Wahyuni, Rahmawati (POLTEKKES KEMENKES MANADO, 2022)
Background: Technique Effleurage Massage is a massage technique in the form of a light massage using the fingers, done on the back. The purpose of this research is to know the technical comparison effleurage massage on reducing pain in postpartum mothers at A.W. Sjahranie Samarinda. Method: Quasi experimental design research using two group pretest posttest design. The number of normal postpartum mothers at Abdul Wahab Sjahranie Hospital is 168 in 2021. The sampling technique in this study purposive sampling with a total sample of 20 people consisting of 10 people in the control group and 10 people in the intervention group. Results: There are technical comparisons effleurage massage on reducing the pain scale in postpartum mothers with a value of ρvalue 0.003 in the intervention group and ρvalue 0.005 in the control group. Conclusion: Engineering comparison effleurage massage effect on reducing the pain scale in postpartum mothers. The post partum mother's pain scale decreased after being given the intervention.